Role of Contrast in Ultrasonography: significance, types, benefits, and limitations. A comprehensive review - Rosiak, Krzysztof; Waloch, Kamil; Uszok, Zofia; Łepik, Michał; Płeska, Kacper; Reguła, Kacper; Piaszczyński, Szymon; Czajka, Andrzej; Wojtania, Joanna; Szymański, Bartłomiej (Journal of Education, Health and Sport, 2024)
Contrast-enhanced ultrasonography (CEUS) has revolutionized diagnostic imaging by significantly improving the accuracy and capabilities of ultrasound technology. By utilizing contrast agents, CEUS offers enhanced visualization of blood flow, superior detection of vascular diseases, and delineation of pathological from healthy tissues. Real-time imaging capabilities afforded by CEUS have been shown to be instrumental in guiding interventions and assessing treatment efficacy, thereby contributing to personalized patient care and improved clinical outcomes. This document provides a comprehensive review of the current benefits, limitations, and future directions of contrast-enhanced ultrasonography. It acknowledges the potential for allergic reactions, the necessity for specialized training, high costs, and the occurrence of image artifacts as drawbacks, while also anticipating advancements in targeted agents and imaging techniques. Moreover, the document emphasizes the need for ongoing research to evaluate the long-term safety and efficacy of contrast agents and their impact across various medical disciplines. Despite the challenges, the integration of CEUS into clinical practice holds enormous potential to further refine diagnostic processes and enhance patient management.